Enhanced reduction in cell viability by hyperthermia induced by magnetic nanoparticles - Héctor L Rodríguez-Luccioni (Dove Medical Press, 2011)
Héctor L Rodríguez-Luccioni, Magda Latorre-Esteves, Janet Méndez-Vega, Orlando Soto, Ana R Rodríguez, Carlos Rinaldi, Madeline Torres-LugoDepartment of Chemical Engineering, University of Puerto Rico, Mayagüez 00681, Puerto RicoAbstract: Colloidal suspensions of iron oxide magnetic nanoparticles are known to dissipate energy when exposed to an oscillating magnetic field. Such energy dissipation can be employed to locally raise temperature inside a tumor between 41°C and 45°C (hyperthermia) to promote cell death, a treatment known as magnetic fluid hyperthermia (MFH). This work seeks to quantify differences between MFH and hot-water hyperthermia (HWH) in terms of reduction in cell viability using two cancer cell culture models, Caco-2 (human epithelial colorectal adenocarcinoma) and MCF-7 (human breast cancer). Magnetite nanoparticles were synthesized via the co-precipitation method and functionalized with adsorbed carboxymethyl dextran. Cytotoxicity studies indicated that in the absence of an oscillating magnetic field, cell viability was not affected at concentrations of up to 0.6 mg iron oxide/mL. MFH resulted in a significant decrease in cell viability when exposed to a magnetic field for 120 minutes and allowed to rest for 48 hours, compared with similar field applications, but with shorter resting time. The results presented here suggest that MFH most likely induces apoptosis in both cell types. When compared with HWH, MFH produced a significant reduction in cell viability, and these effects appear to be cell-type related.Keywords: magnetic fluid hyperthermia, carboxymethyl dextran magnetite, cell death, apoptosis